FROM GEOPOLITICAL TO ASTROPOLITICAL TENSIONS: HOW ESCALATING RIVALRIES SHAPE THE SPACE STRATEGIES OF THE UNITED STATES, RUSSIA, AND CHINA - Šljivančanin, Milica (Political Review, 2026)
This paper analyzes the transformation of outer space from a domain of scientific exploration into a space of intense geopolitical competition among leading global powers. The aim of the study is to determine how heightened geopolitical tensions in the period from 2014 to 2024 have influenced the redefinition of the space strategies of the United States of America, the Russian Federation, and the People’s Republic of China. Through a comparative analysis of the space strategies of these states, the paper addresses the question of how outer space is becoming an arena in which technological advancement, military power, and ideological influence intersect and compete. The research is based on a combination of geopolitical and astropolitical theoretical frameworks, applying the realist paradigm  of  international  relations  and a threefold methodological approach that includes comparative analysis, content analysis of official strategic documents, and theoretical–interpretative analysis. Particular attention is devoted to examining how space exploration technologies are becoming instruments of both soft and hard power, while the boundary between their civilian and military use is gradually eroding. The results of the study indicate that although the United States continues to maintain a dominant position thanks to long-term investments and institutional infrastructure, the growing ambitions of China and Russia’s attempts to revitalize its space programs signal a process of the multipolarization of space. In conclusion, outer space is emerging as one of the key arenas of future geopolitical conflicts, but also as a field for redefining international relations and security paradigms in the twenty-first century.
Keywords: geopolitics; astropolitics; realism; United States; Russia; China; strategies; militarization of space; global relations